Why human societies adopt rigid moral rules: The efficiency–robustness trade-off - Julien Lie-Panis; Léo Fitouchi; Nicolas Baumard; Jean-Baptiste André (Proceedings of the National Academy of Sciences, 2026)
Humans are capable of remarkably flexible moral judgment. Yet societies rely on rigid rules—obligations and prohibitions that apply categorically, even when case-by-case reasoning could yield better outcomes. Why would a species capable of flexibility bind itself to rigid rules? We propose that rigid rules arise as social technologies for managing ambiguity about noncooperation. People often have legitimate reasons for failing to cooperate, yet those reasons are typically opaque to observers, allowing opportunists to disguise selfishness as justified hardship. We formalize this idea with a game-theoretic model. Two cooperative equilibria emerge: a flexible norm that accommodates legitimate excuses but is vulnerable to exploitation, and a rigid norm that closes this loophole by mandating cooperation even when inefficient. Comparing these equilibria reveals an efficiency–robustness trade-off: Flexibility maximizes welfare when trust is secure, whereas rigidity preserves cooperation when trust is fragile. This explains why rigid rules prevail in interactions with strangers, formal institutions, or in tight societies, while flexibility is more common when trust is secure.